Sepsis in Obstetrics. Issue 4 (July 2017) - N/A,
Abstract : Sepsis is a significant cause of maternal morbidity and mortality in the United States. Knowledge of the latest evidence and clinical guidelines will support best practices to promote optimal care for mothers and babies.